The Influence of Transformational Leadership on Enhancing Student Attendance and Engagement in Secondary Schools - Nurlina, Nurlina; Hardianti, Hardianti; Susianti, Susi (Educia Journal, 2024)
This study examines the impact of school leadership on student attendance and engagement, addressing gaps in the literature regarding how leadership styles influence these critical educational outcomes. Employing a quantitative correlational research design, data were collected from 300 secondary school students and 50 school leaders in Makassar City using stratified random sampling. Leadership styles were measured using the Multifactor Leadership Questionnaire (MLQ), while student engagement was assessed with the Student Engagement Scale (SES). Attendance data were retrieved from official school records. Results revealed significant positive correlations between transformational leadership and both student attendance (r = 0.62, p < 0.001) and engagement (r = 0.75, p < 0.001). Multiple regression analysis demonstrated that transformational leadership significantly predicted attendance (β = 0.58, p < 0.001) and engagement (β = 0.72, p < 0.001), highlighting its critical role in fostering positive student outcomes. Furthermore, the findings emphasized the relevance of transformational leadership in promoting equity by improving attendance and engagement across diverse school contexts. This study provides practical implications for educational policies and leadership training programs, advocating for a stronger focus on transformational leadership practices. The results also contribute to the growing body of evidence linking effective leadership with improved student outcomes, offering insights for future research on leadership interventions.